Value relevance of mandated market risk exposure disclosure : value-at-risk. - Sentosa, Adi. (2008)
This paper investigates the value relevance of Value-at-Risk. It was found that Value-at-Risk is associated with weaker earnings-returns relation. Investors perceive the earnings of firms with considerable market risk exposure to be less persistent and thus lower their expected rate of returns.